A Schulman adds masterbatch plant in Turkey and expands compounding in Belgium. Issue 6 (June 2015) - Unknown
Abstract : Masterbatch manufacturer A. Schulman, Inc has revealed plans to establish a new masterbatch production plant in Turkey. When fully operational, the new facility will produce approximately 40 million lbs (c. 18 000 tonnes) annually of the company's premium additive, white and breathable masterbatches for food and industrial packaging customers in Turkey and other fast-growing countries in the Middle East and North Africa.